Thermal properties and drying shrinkage performance of palm kernel shell ash and rice husk ash-based geopolymer concrete - Abdullah, Mohd Na’im; Mustapha, Faizal; Yusof, Nurul ‘Izzati; Khan, Tabrej; Sebaey, Tamer A. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study aims to develop suitable formulations of geopolymer concrete (GPC) by varying the percentages of the geopolymer with aggregates and evaluating the performances in thermal and mechanical properties of palm kernel shell ash (PKSA)-GPC compared to rice husk ash (RHA)-GPC and ordinary Portland cement concrete (OPCC). Preliminary tests were conducted to select the best mix design ratios before casting the specimens. Then, the performance of the PKSA-GPC, RHA-GPC and OPCC specimens was evaluated based on their thermal performance and drying shrinkage. The mix designs of PKSA-GPC 70:30, PKSA-GPC 60:40, PKSA-GPC 50:50 and PKSA-GPC 66.6:33.3 were found to produce an acceptable consistency, rheological and thixotropic behaviour for the development of the GPC. PKSA-GPC showed a better thermal performance than the RHA-GPC and OPCC due to their strong and dense intumescent layers and slow temperature increment upon exposure to a high flame temperature from ambient temperature to 169 °C. The low molar ratio of the Si/Al present in the PKSA-GPC created a thermally stable intumescent layer. In the drying shrinkage test, PKSA-GPC 60:40 and RHA-GPC 60:40 shared an equal drying shrinkage performance (5.040%) compared to the OPCC (8.996%). It was observed that microcrack formation could significantly contribute to the high shrinkage in the PKSA-GPC 50:50 and RHA-GPC 70:30 specimens. The findings of this study show that PKSA could be incorporated into GPC as a fire-retardant material due to its capability of prolonging the spread of fire upon ignition and acting as an alternative to the conventional OPCC.